Motherhood beliefs across sex, age, education and parenthood - V.E. Olalde-Mathieu; G.L. Licea-Haquet; A. Reyes-Aguilar (Social Sciences and Humanities Open, 2024)
Motherhood is a cultural process that has traditionally anchored women's identities in their ability to nurture infants and children (Ross, 2018). As a cultural and dynamic construct, it not only shapes women's social identity but also plays a pivotal role in influencing gender roles. The aim of the present study is to analyze the psychometric properties of the Motherhood Belief Scale, which explore Sense of Life and Social Duty as two dimensions of motherhood in a general sample (n = 6207) with different sex, age, education, and parenthood status. The reliability of the Motherhood Belief Scale in our sample showed low fitted scores, low variability, and a floor-like effect, which was more eminent for the Social Duty dimension. These findings showed differences in motherhood beliefs across sex, age, education, and parenthood. Additionally, we explored answers for two open questions about motherhood with a sentiment analysis which showed a more significant bias to positive emotional valence in people without professional studies out professional studies. These findings suggest a more stereotypical view of motherhood in populations with low education, very young or elderly, men, and with parenthood status.